Industri Wisata Halal di Indonesia: Produk Kapitalisme Sampai Dengan Fundamentalisme Agama - Admadi Balloara Dase (Institut Agama Kristen Negeri Toraja, 2021)
This paper tries to explore the concept initiated by tourism industry experts, using the critical discourse analysis method. Critical Discourse Analysis is intended to dismantle the ideology behind halal tourism. Jean Baudrillard's Simulation concept is used to dissect the construction of halal tourism experts who attach the